A Study into the Thinning Intensities for Plantation Sal (Shorea robusta) - Mathauda, G. S. (Indian Forester, 1953)
In order to study the development of plantation sal under different grades of thinning, a set of 3 sample plots was laid out in a 5-year old crop in Kalimpong Division of West Bengal, in 1930. The plots were measured and thinned in 1936, 1941, 1946 and 1951. The investigation has been described, the data analysed and results discussed. It appears that for top quality sal plantations maximum basal area and total volume production is obtained under the 'C/D' grade of thinnings. The 'D' grade gives approximately equal volume production, whereas the 'D/E' grade is decidedly inferior to either in this respect. An increase in thinning intensity, however, accelerates the development of average diameter and pushes up more trees into the upper diameter classes.